Investigation on transport related biogas utilization - Kovács, Viktória B.; Török, Ádám (Transport, 2010)
Due to an increase in demand for energy and the mobility of the human population as well as in order to keep sustainable development, there is a major need to utilize alternative energy sources. The use of biogases as a source of renewable energy could provide an effective and alternative way to fulfil a remarkable part of this demand for energy. As biogases have high inert content, their heating value is low. The energetic utilization of these low heating value renewable gaseous fuels is not fully worked out yet because their combustion characteristics significantly differ from the liquid fuels that are used nowadays in transportation, and in this way, they are not usable or their utilization is limited in devices with conventional equipment. Thus, theoretical and experimental analysis was made to investigate the usability of biogases. First published online: 24 Jun 2011